Comprehensive Analysis of UAV Flight Parameters for High Resolution Topographic Mapping. Issue 1 (May 2021) - Muhammad, M; Tahar, K N
Abstract: Unmanned Aerial Vehicles (UAVs) are aircrafts without pilot on board, which are controlled by the ground station or transmitter. The ability of UAVs to provide high-resolution imageries and accurate positioning makes it the best platform as compared to satellite images. Therefore, UAVs can speed up the topographic works, especially during data collection. Topographic mapping has been used by many agencies such as the government, private, and military. Furthermore, the geotagged high resolution UAV images can provide accurate results using Ground Control Points (GCPs). UAV flight parameters, such as flight altitude and overlap and sidelap percentages, can affect the topographic map result derived from the UAV images. The optimal flight altitude and overlap and sidelap percentages based on the specific topographic surface need to be investigated to produce an accurate topographic map. The aim of this study is to assess the accuracy of topographic maps from different flight parameters. There are two objectives to achieve the aim; i.e., to produce photogrammetric products from different overlaps and sidelaps as well as analyze the photogrammetric products with ground survey data. The selected flight altitude in this study is 60 m. However, the overlap percentages are 70%, 80%, and 90% and the sidelap percentages are 50%, 60%, and 70%. GCPs and Check Points (CPs) will be established using global navigation satellite system (GNSS) techniques, where the global positioning system (GPS) receiver is capable of real-time kinematic (RTK) to receive real-time data correction from the continuously operating reference stations (CORS) in different locations. This study will analyze the topographic results at different overlap and sidelap percentages using Root Mean Square Error (RMSE). The expected outcome of this study includes the comparison coordinates between CP coordinates and ground survey data coordinates, different digital terrain models (DTM), and different topographic maps.